The Impact of Gelora Manahan Solo Renovation on Persis Solo Potential Sport Tourism - Putra, Febrianur Ibnu Fitroh Sukono; Aqmala, Diana; Praswati, Aflit Nuryulia (Jurnal Penelitian Ekonomi dan Bisnis, 2021)
Football is an extraordinary type of tourism in the sports sector which is very popular in the world, which the matches of football teams being tourist attraction objects that provide benefits for the organizers of the competition and the football club itself. Indonesian football competition has been participated by many professional teams, one of them is PERSIS Solo who participated in league 2. This research aims to analyze the potential interest in PERSIS Solo sports tourism in Surakarta after the renovation program of the Manahan Solo Stadium. This type of research is descriptive qualitative. The analysis method uses SWOT (strengths, weaknesses, opportunities, and threats). Internal environment analysis will focus on strengths and weaknesses, while the external environment will be the focus on opportunities and threats. The results showed that PERSIS Solo was in the quadrant I position, so the management of the club could take a policy with utilizing the strength of the internal environment to maximize existing market opportunities.  Keywords:Football Sport, Persis Solo, SWOT Analysis, Special Interest Tourism